Development of gradient diffusion strips to identify the potentiating effect of antimicrobial compounds against multidrug-resistant Klebsiella pneumoniae strains - Likhachev I.V.; Kaftyreva L.A.; Samoilova A.A.; Kraeva L.A.; Mikhailov N.V. (Клиническая микробиология и антимикробная химиотерапия, 2024)
Objective.